Towards Multi-Criteria Prioritization of Best Practices in Research Artifact Sharing - Damasceno, Carlos Diego Nascimento; Melo, Isotilia Costa; Strüber, Daniel (Anais do Workshop de Práticas de Ciência Aberta para Engenharia de Software (OpenScienSE), 2021)
Research artifact sharing is known to strengthen the transparency of scientific studies. However, in the lack of common discipline-specific guidelines for artifacts evaluation, subjective and conflicting expectations may happen and threaten artifact quality. In this paper, we discuss our preliminary ideas for a framework based on quality management principles (5W2H) that can aid in the establishment of common guidelines for artifact evaluation and sharing. Also, using the Analytic Hierarchy Process, we discuss how research communities could join efforts to aid the guidelines’ adequacy to research priorities. These combined methodologies constitute a novelty for software engineering research which can foster research software sustainability.